2019
DOI: 10.3847/1538-4357/ab40bb
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Radio-wave Scattering and the Interpretation of Solar Radio Emission Observations

Abstract: The observed properties (i.e., source size, source position, time duration, decay time) of solar radio emission produced through plasma processes near the local plasma frequency, and hence the interpretation of solar radio bursts, are strongly influenced by propagation effects in the inhomogeneous turbulent solar corona. In this work, a 3D stochastic description of the propagation process is presented, based on the Fokker-Planck and Langevin equations of radio-wave transport in a medium containing anisotropic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
185
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(206 citation statements)
references
References 66 publications
19
185
2
Order By: Relevance
“…The Gaussian decay was in contrast to the exponential decay used in previous works (e.g., Aubier and Boischot, 1972;Barrow and Achong, 1975;Mel'Nik et al, 2011) although similar HWHM decay times were found. The decay time r decay ∝ f 0.89±0.15 compares very well with comparisons of decay times all the way down to kHz frequencies, shown by Kontar et al (2019), that could be fit with a power-law that had a spectral index close to 1. The rise and decay times also showed a very strong correlation, indicating that one process dominates both time scales at LOFAR frequencies.…”
Section: Low Frequency Burstssupporting
confidence: 80%
See 3 more Smart Citations
“…The Gaussian decay was in contrast to the exponential decay used in previous works (e.g., Aubier and Boischot, 1972;Barrow and Achong, 1975;Mel'Nik et al, 2011) although similar HWHM decay times were found. The decay time r decay ∝ f 0.89±0.15 compares very well with comparisons of decay times all the way down to kHz frequencies, shown by Kontar et al (2019), that could be fit with a power-law that had a spectral index close to 1. The rise and decay times also showed a very strong correlation, indicating that one process dominates both time scales at LOFAR frequencies.…”
Section: Low Frequency Burstssupporting
confidence: 80%
“…Bian et al (2019) modeled the scattering process using a Fokker-Planck equation and were able to reproduce the time profile but not the inverse frequency dependence of the decay time, which they concluded was down to the exclusion of a large-scale refractive term. Kontar et al (2019) recently extended the work of Bian et al (2019) but treated the scattering in the anisotropic domain, with the dominant effect being perpendicular to the heliospheric radial domain (Kontar et al, 2017). As well as explaining temporal profiles, Kontar et al (2019) used ray-tracing simulations to explain the increase in source sizes, finding a scattering increase in the FWHM around 1.1 R ⊙ at 35 MHz, although this value will depend upon the size of the density fluctuations from event to event.…”
Section: Radio Wave Propagationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, density fluctuations can cause scattering of the radio waves during propagation, which is also not included in the simulation. The duration of the radio emission at a given frequency can also be broadened by scattering (Kontar et al 2019). The increase of the duration may mix the segments of the discontinuity and weaken the significance of fine structures.…”
Section: Conclusion and Discussionmentioning
confidence: 99%